2020
DOI: 10.18016/ksutarimdoga.vi.579695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vermicompost on Macro and Micro Nutrients of Lettuce (Lactuca Sativa Var. Crispa) Under Salt Stress Conditions

Abstract: This study was conducted in order to determine the effect of vermicompost (V) on macro and micro nutrients of lettuce (Lactuca sativa Var. crispa) exposed to salt stress (SS). V doses; 0 (V0), 2.5% (V1) and 5% (V2) (w/w) and salt stress levels; control (SS0) (0 dS m-1 NaCl), medium salt stress (SS4) (4 dS m-1 NaCl), severe salt stress (SS8) (8 dS m-1 NaCl) were used. In order to make evaluation in terms of the nutrients, plants were kept under controlled conditions (relative humidity 50-55%, daytime/night time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The overlay visualization was used to show the trends in keywords used in the topic. For instance, the gradient color shown on the map, from blue to yellow, reveals the freshness of publications [ 73 ] and reveals recently appearing keywords. Before the keyword analysis, the authors standardized the keywords manually because based on [ 74 ] different expressions of the same keywords might cause errors in the findings.…”
Section: Methodsmentioning
confidence: 99%
“…The overlay visualization was used to show the trends in keywords used in the topic. For instance, the gradient color shown on the map, from blue to yellow, reveals the freshness of publications [ 73 ] and reveals recently appearing keywords. Before the keyword analysis, the authors standardized the keywords manually because based on [ 74 ] different expressions of the same keywords might cause errors in the findings.…”
Section: Methodsmentioning
confidence: 99%
“…Biochar is also an important organic material and its application under saline conditions improves root growth, dry matter production, leaf area, and yield compared to control conditions [168]. The addition of organic fertilizers (Vermicompost and biogas slurry) also increases the availability of nutrients (Ca, Fe, Mg, Mn, K, and Zn) and reduces the accumulation of toxic ions (Cl − and Na + ), resulting in a significant increase in plant height, dry matter and final productivity [162][163][164]. Another group of authors also found that under saline conditions, organic fertilizers improved the RWC, stomata conductance, chlorophyll synthesis, and activity of antioxidants (APX, CAT, and SOD) that decreased MDA production and electrolyte leakage, thereby preventing the toxic effects of salinity on plants [165][166][167].…”
Section: Role Of Organic Fertilizers To Mitigate Salinity Stressmentioning
confidence: 99%